Introducing the Newly Isolated Bacterium Aneurinibacillus sp. H1 as an Auspicious Thermophilic Producer of Various Polyhydroxyalkanoates (PHA) Copolymers-2. Material Study on the Produced Copolymers - Sedlacek, Petr; Pernicova, Iva; Novackova, Ivana; Kourilova, Xenie; Kalina, Michal; Kovalcik, Adriana; Koller, Martin; Nebesarova, Jana; Krzyzanek, Vladislav; Hrubanova, Kamila; Masilko, Jiri; Slaninova, Eva; et al. (Polymers, 2020)
Aneurinibacillus sp. H1 is a promising, moderately thermophilic, novel Gram-positive bacterium capable of the biosynthesis of polyhydroxyalkanoates (PHA) with tunable monomer composition. In particular, the strain is able to synthesize copolymers of 3-hydroxybutyrate (3HB), 4-hydroxybutyrate (4HB) and 3-hydroxyvalerate (3HV) with remarkably high 4HB and 3HV fractions. In this study we performed an in-depth material analysis of PHA polymers produced by Aneurinibacillus sp. H1 in order to describe how the monomer composition affects fundamental structural and physicochemical parameters of the materials in the form of solvent-casted films. Results of infrared spectroscopy, X-ray diffractometry and thermal analysis clearly show that controlling the monomer composition enables optimization of PHA crystallinity both qualitatively (the type of the crystalline lattice) and quantitatively (the overall degree of crystallinity). Furthermore, resistance of the films against thermal and/or enzymatic degradation can also be manipulated by the monomer composition. Results of this study hence confirm Aneurinibacillus sp. H1 as an auspicious candidate for thermophilic production of PHA polymers with material properties that can be tuned together with their chemical composition by the corresponding adjustment of the cultivation process.
Keywords: crystallinity; Aneurinibacillus sp.; thermophiles; P(3HB-co-4HB); polyhydroxyalkanoates; P(3HB-co-3HV-co-4HB)